2015
DOI: 10.1016/j.drugalcdep.2015.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

A reexamination of medical marijuana policies in relation to suicide risk

Abstract: Objectives Previous research has suggested that medical marijuana policies lead to reductions in suicide rates. In this study, we further investigate the association between these policies and within-state changes in suicide risk. Methods Data on suicide deaths (n=662,993) from the National Vital Statistics System Multiple Cause of Death files were combined with living population data. Fixed-effects regression methods were employed to control for state differences in suicide rates and national and state secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…reported steeper declines in suicides among males aged 20–30 in US states that legalized MM than in those that had not . This finding was not supported by another analysis that controlled for differences between states or the failure to find an association between suicide rates and the number of MM patients in US states between 2004 and 2010 .…”
Section: The Effects Of Medical Marijuana Lawsmentioning
confidence: 89%
“…reported steeper declines in suicides among males aged 20–30 in US states that legalized MM than in those that had not . This finding was not supported by another analysis that controlled for differences between states or the failure to find an association between suicide rates and the number of MM patients in US states between 2004 and 2010 .…”
Section: The Effects Of Medical Marijuana Lawsmentioning
confidence: 89%
“…To model the living population, we combined data from the annual American Community Survey (ACS) for the years 2001 to 2010, obtained from the Integrated Public Use Microdata Series maintained by the Minnesota Population Center (Ruggles et al., ). As the ACS was not administered annually prior to 2000, we used data from 1% samples of the 1990 and 2000 Census to estimate data for years 1991 through 1999 using a linear interpolation procedure fully described elsewhere (Grucza et al., , ). Briefly, this was accomplished by creating a single record for each possible combination of covariate parameters in each census data set (i.e., each combination of year, state, race/ethnicity, sex, age group, and education) and assigning that record a weight corresponding to the population for that group.…”
Section: Methodsmentioning
confidence: 99%
“…State medical cannabis legalisation associated with significant 9–11% reductions in suicide among young men (age 20–39) in one study . This effect lost significance after controlling for race/ethnicity and state tobacco policies .…”
Section: Resultsmentioning
confidence: 96%
“…In Colorado, the proportion of suicide decedents who test positive for THC has also increased since before non-medical legalisation [19], but this trend has not been compared against a control, and this measurement is subject to the same inference limitations as THC-positive driver fatalities. Longitudinal studies comparing suicide rates in medical cannabis states to control states have not found significant between medical cannabis legalisation and suicides [64,65].…”
Section: Mental Health and Cognitionmentioning
confidence: 99%